Violencia política sexual: una conceptualización necesaria. - Maldonado Garay, Jocelyn (Nomadías, 2019)
The following article is theoretically responsible for constructing the concept of "Sexual Political Violence" (VPS) in order to position it as a category of analysis for gender theory and social sciences, making a distinction regarding sexual violence. This theoretical construction is carried out based on concrete facts such as armed conflicts and their bodily and social effects, considering how it relates to war, either in practical or discursive terms, whose execution is associated with political purposes and, therefore, to a rational decision.